2017
DOI: 10.1039/c6nj02753a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytotoxicity by a benzothiazole-containing cisplatin derivative in breast cancer cells

Abstract: A synergic acting cisplatin derivative, made via conjugating CJM126 with cisplatin, was synthesized and delivered using liposomes to inhibit tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 66 publications
2
4
0
Order By: Relevance
“…As shown in Figure F,G, FeTB 2 obviously acts on the G2/M phase of the cell cycle. Especially, the cell percentage in the S phase increases from 37.02% to 42.73% and decreases from 57.24% to 34.86% in the G0/G1 phase; this is highly consistent with our previous study that benzothiazole derivatives act as a DNA binding agent to prevent DNA replication . In addition, the results further show that FeTB 2 @DHA-INPs also interferes with the cell cycle in the G2/M phase.…”
Section: Results and Discussionsupporting
confidence: 91%
“…As shown in Figure F,G, FeTB 2 obviously acts on the G2/M phase of the cell cycle. Especially, the cell percentage in the S phase increases from 37.02% to 42.73% and decreases from 57.24% to 34.86% in the G0/G1 phase; this is highly consistent with our previous study that benzothiazole derivatives act as a DNA binding agent to prevent DNA replication . In addition, the results further show that FeTB 2 @DHA-INPs also interferes with the cell cycle in the G2/M phase.…”
Section: Results and Discussionsupporting
confidence: 91%
“…3d). The cellular uptake of the present LPs can be blocked by pretreating the MCF-7 cells with PEG-lecithin shell, 26 which confirmed that the internalization of the Pt/Fe 3 O 4 @SP-PLGA LPs was accelerated by the specific compatibility between phospholipids and the cell membrane.…”
Section: Intracellular Uptakesupporting
confidence: 66%
“…A novel strategy used to obtain protective layers is coating of the magnetite with a layer to obtain high stability under extreme conditions, a natural porous structure, and a platform for chelating groups. 170 Administrating an encapsulation of Fe 3 O 4 NPs into drug delivery systems such as liposomes, [171][172][173][174][175] nanomicelles, 176,177 or inorganic mesoporous silica nanoparticles [178][179][180][181] can adequately exploit their favourable features in drug delivery stimulated by pH/T/light/ultrasound. These combination nanocarriers have also received considerable attention to trigger cargo release under the effect of a high-frequency alternating magnetic eld (AMF).…”
Section: Magnetic Eld Responsive Drug Deliverymentioning
confidence: 99%